Analisis Pengendalian Persediaan Bahan Baku Packing Menggunakan Metode Joint Replenishment Problem - Suseno Suseno; Pitri Riyanti (Fakultas Teknik, 2018)
PT Out Of Asia is an exporting company that produces handicraft products. All products in the company are semi-finished products from suppliers who performed the finishing and packing stage. The production process system is done by the company varies according to the demand of the consumer, so the raw material of packing needed also vary. However, the increasing number of consumer demand is increasingly binding, it will also increase the demand for packing raw materials, so it is necessary to control the supply of raw materials packing to minimize the cost of raw material inventory according to storage capacity and packing production capability. In addition, ordering of raw materials can be done in combination to save raw material inventory. The method used in this research is Joint Replenishment Problem (JRP) and (Economic Order Quantity (EOQ) method, to compare total inventory cost using Joint Replenishment Probe (JRP) and Economic Order Quantity (EOQ) method. The research shows that total cost the minimum inventory using Joint Replenishment Problem (JRP) method is Rp 1,180,246,601 / year compared to use the Economic Order Quantity (EOQ) method of Rp 4,326,163,356 / year, with the difference of comparison using JRP and EOQ of Rp 3,145,916,750/ year